2014
DOI: 10.1111/bjd.13129
|View full text |Cite
|
Sign up to set email alerts
|

High‐frequency ultrasonography but not 930‐nm optical coherence tomography reliably evaluates melanoma thickness in vivo : a prospective validation study

Abstract: HFUS is a reliable and reproducible noninvasive method for assessing melanoma thickness. Routine use of HFUS may allow single-step excision of equivocal melanocytic lesions, with surgical margins determined by in vivo assessment of tumour thickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 37 publications
1
41
2
1
Order By: Relevance
“…Therefore, Wortsman et al recommend that a physician a dermatologist or a radiologist-should be the person to perform ultrasonic examination [25]. The differences between mT measurements by two experienced dermatologists were found to be irrelevant in our study as well as in studies by other researchers [13,14]. In addition, we found non-significant differences between mT and aT measurements regarding the analyzed MST.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…Therefore, Wortsman et al recommend that a physician a dermatologist or a radiologist-should be the person to perform ultrasonic examination [25]. The differences between mT measurements by two experienced dermatologists were found to be irrelevant in our study as well as in studies by other researchers [13,14]. In addition, we found non-significant differences between mT and aT measurements regarding the analyzed MST.…”
Section: Discussioncontrasting
confidence: 53%
“…Compared to high frequency US, optical coherence tomography has a lower accuracy in predicting mT [14]. Therefore, high frequency US is still an advanced tool for the estimation of CM thickness in vivo in cases of tumours of around 1 mm and thicker.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…63 On the other hand, the wavelength of the OCTdevice influences the penetration depth, and studies have shown that high frequency ultrasound is superior to OCT-scans at 930 nm in determining tumor thickness. 64 A recent study has shown OCT at 1300 nm to be slightly more accurate in assessing tumor thickness, though both technologies tend to overestimate thin tumors (<0.2 mm) and underestimate thick tumors (>0.7 mm) compared to histology. 65 In a descriptive study using HD-OCT in pigmented lesions, melanomas have, compared to benign lesions, a higher frequency of fusion of rete ridge, pagetoid cells, and junctional and/or dermal nests with atypical cells.…”
Section: Nonmelanoma Skin Cancermentioning
confidence: 99%
“…Thickness of the melanoma along with the number of mitoses and presence or absence of ulceration shows the greatest correlation with the degree of 5-year survival [2]. So far, individual studies have addressed the issue of pre-operative melanoma evaluation using ultrasonography, high-frequency ultrasonography (HFUS) and optical coherence tomography (OCT) [3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%